166. Comparison of Oral Fluoroquinolones to Alternative Oral Agents for Definitive Step-Down Therapy in Gram-Negative Bloodstream Infections - Cho, Christian Y (Open Forum Infect Dis, 2019)
BACKGROUND: During the management of Gram-negative bloodstream infections (GN BSIs), definitive oral step-down therapy is often utilized. Fluoroquinolones (FQs) are commonly utilized due to excellent bioavailability; however, comparative evidence to oral trimethoprim/sulfamethoxazole (TMP/SMX) or β-lactams (BLs) are limited. METHODS: This multicenter, retrospective cohort included patients ≥18 years of age who had a GN BSI and received oral FQ, BL, or TMP/SMX as definitive oral step-down therapy for >33% of their total treatment duration. Patients were excluded if received ˂7 days or >17 days of total therapy, or had polymicrobial bacteremia. The primary outcome was treatment failure within 90 days. Treatment failure was a composite endpoint including both all-cause mortality and recurrence of infection. Secondary outcomes included all-cause and infection-related readmissions at 30 days. RESULTS: A total of 220 patients were included (FQ n = 106, BL n = 96, SMX/TMP n = 18). Patients were elderly (median age 70 years; IQR 59–79) and had a median Pitt bacteremia score of 1 (IQR 0–2). The most common pathogens were E. coli (58.2%) and K. pneumoniae (17.3%) and the primary source of infection was urinary (70%). Majority of BL use consisted of cephalexin (44.7%) and cefuroxime (21.3%) while FQ use was mostly ciprofloxacin (69.8%). Infectious diseases consultations were associated with 52.8%, 39.6%, and 72.2% of the prescribed FQ, BL, and SMX/TMP, respectively. Overall median intravenous, oral, and total effective antibiotic durations were 3.9, 9, and 13 days, respectively, and were similar between each group. Ninety day treatment failure rates were 9.5% in the FQ group vs. 14.6% in the BL group (P = 0.27) and 0% in the TMP/SMX group (P = 0.35). All-cause and infection-related readmissions were similar between FQ, BL, and TMP/SMX: (25.5%, 27.1%, 16.7%; P = 0.73) and (4.7%, 5.2%, 5.6%; P = 1.0), respectively. CONCLUSION: We identified similar treatment failure rates between oral FQs, BLs, and TMP/SMX. Oral step-down therapy with BLs may be a promising FQ-sparing option for the definitive treatment of GN BSIs. Limitations to TMP/SMX efficacy should be interpreted with caution due to the small sample size. Further investigations into optimal and tolerable oral dosing of such agents are needed. DISCLOSURES: All authors: No reported disclosures.